Áhættuþættir kransæðasjúkdóms meðal karla og kvenna á Íslandi: niðurstöður úr hóprannsókn Hjartaverndar 1967-1985 - Guðmundur Þorgeirsson; Davíð Davíðsson; Helgi Sigvaldason; Nikulás Sigfússon (Læknafélag Íslands, Læknafélag Reykjavíkur, 2007)
Neðst á síðunni er að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open The Reykjavík Study 1967-1985: Risk factors for coronary heart disease mortality have been investigated in a prospective study of 8001 randomly selected Icelandic men and 8468 women. The men were aged 34-64 and the women 34-76 at the time of their first examination. After followup from 2-17 years 1140 (14.2%) of the men and 537 (6.3%) of the women had died. Coronary heart disease accounted for 43% of the mortality among the men, cancer 27% and cerebrovascular disease 7%. This distribution is in contrast to what was found among the women. Coronary heart disease accounted for 19.4% of the mortality, cancer 42.3% while the relative contribution of cerebrovascular mortality was similar. The effects of various factors were assessed simultaneously with multivariate survival analysis using the Cox's proportional hazard model. Age, serum total cholesterol, triglycerides, smoking and systolic blood pressure were all significant independent risk factors for coronary heart disease mortality in both sexes. Fasting blood sugar was of borderline significance, reaching significance among men, but not among women. However, since the women have much lower risk of dying from coronary heart disease than the men the absolute risk associated with each of the risk factors is much lower in the women. Samband hinna ýmsu áhættuþátta og dánartíðni úr kransæðasjúkdómi var kannað í úrtaki 8001 karls og 8468 kvenna sem hafa komið að minnsta kosti einu sinni til skoðunar í framskyggndri hóprannsókn Hjartaverndar. Karlarnir voru á aldrinum 34-74 ára og konurnar 34-76 ára við fyrstu heimsókn í Hjartavernd. Í árslok 1985 hafði þessum hópi fólks verið fylgt í tvö til 17 ár. Þá höfðu 1140 (14,2%) karlmannanna og 537 (6,3%) kvennanna látist. Tíðni dánarorsaka var mjög ólík meðal kynjanna. Þannig stöfuðu 43% dauðsfalla karla af kransæðasjúkdómi, 27% af illkynja sjúkdómum og 7% af heilablóðfalli. Illkynja sjúkdómar voru algengasta dánarorsök kvenna ...